(untitled) (Journal of history, 2018)
During the Great Migration of Nations in Eurasia, the Byzantine Empire established links with neighboring barbarian tribes and kingdoms. One of the tribes neighboring the Eastern Roman Empire was the Slavs. In the IV-VII centuries the Slavs entered the Byzantine territory, which was due to this empire. Recently, the national historiography conducted research on the foreign policy of the Byzantine Empire and political relations with neighboring tribes. The scientific article – is one such work, which focuses on the political, social relations and military traffic between the Byzantine Empire and the neighboring Slavic tribes during the Great Migration. The appearance of the Slavs in the South-Eastern Europe and their political, commercial and social relations with Byzantium are mass processes. Analyzing the early medieval sources and different scientific materials, studied the history of the Slavic peoples, strengthening and development, tradition, custom and social history of south-eastern Slavs and their relations of the Byzantine Empire. Scientific work includes the policy of the emperors of the Byzantine Empire against the Slavic tribes. The article defines the political and historical significance of the relations of the Slavic tribes with Byzantium.